Rhizobacteria consortium improves growth, yield, and phytochemicals in Robusta coffee (Coffea canephora L.) - Suriani, Ni Luh; Al-zharani, Mohammed; Nasr, Fahd A.; Alneghery, Lina M.; Suprapta, Dewa Ngurah; Suarsana, I. Nyoman; Resiani, Ni Made Delly; Enshasy, Hesham Ali El; Sayyed, Riyaz; Barasarathi, Jayanthi; Ho, Ting Seng; Yanti, Yulmira (Frontiers in Microbiology, 2025)
IntroductionCoffee is among the most sought-after and valued commodities because it has a high market value and serves as a soothing beverage. However, organically grown coffee remains limited. Most coffee farmers still use agrochemicals which, pose harmful effects. Therefore, alternative methods are needed to produce healthier crops, such as utilizing rhizobacteria, which are environmentally friendly and safe for human health.MethodsThrough this study, rhizobacteria treatment was applied to coffee plants to enhance growth, phytochemical content, and antioxidant activity. The present study aimed to determine the influence of rhizobacteria on the growth, production, and phytochemical content of Balinese robusta coffee plants. The research utilized a randomized group approach with four different treatments, six repetitions, and three units, resulting in a total of 72 experimental plants. F0 represents the control group with untreated soil, while F1, F2, and F3 correspond to treatments with 2% Bacillus nitrificans, 2% Bacillus velezensis, and a consortium of 2% Bacillus nitrificans and 2% Bacillus velezensis, respectively.ResultsThe results indicated that the F1, F2, and F3 treatments showed a notable distinction in comparison to the control. The F3 treatment proved to be the most efficient in enhancing growth, antioxidant activity, alkaloid content, tannin levels, caffeine concentration, and coffee production, whereas the F2 treatment resulted in the highest flavonoid content. Both types of rhizobacteria can generate IAA, facilitate nitrogen fixation, and solubilize phosphorus. Moreover, all four rhizobacteria are capable of colonizing the roots of Robusta Bali coffee.DiscussionThe two rhizobacteria, B. nitrificans and B. velezensis, can function as biofertilizers and biostimulants for Robusta coffee plants in Bali, as they enhance growth, yield, and phytochemical content. When combined, these rhizobacteria produce better results compared to control and single treatments, as they generate a greater amount of biofertilizers and biostimulants. Therefore, these rhizobacteria are highly suitable for supporting sustainable agriculture.